Green Synthesis of Iron Nanoparticles: Application on the Removal of Petroleum Oil from Contaminated Water and Soils - Erika Murgueitio; Luis Cumbal; Mayra Abril; Andrés Izquierdo; Alexis Debut; Oscar Tinoco (Journal of Nanotechnology)
Iron nanoparticles were produced using the extract of mortiño berry (Vaccinium floribundum) (vZVI) as reducing and stabilizer agent. Fresh nanoparticles were characterized using TEM, XRD, and FTIR techniques, while laboratory experiments were conducted to assess the removal of total petroleum hydrocarbons (TPHs) from water and soil after treatment with synthesized nanoscale iron particles. Nanoparticles as produced were spherical in the range of 5–10 nm. After treatment with vZVI nanoparticles, water contaminated with two concentrations of TPHs (9.32 mg/L and 94.20 mg/L) showed removals of 85.94% and 88.34%, respectively, whereas a contaminated soil with a TPHs concentration of 5000 mg/kg treated during 32 h with nanoparticles reached a removal of 81.90%. Results indicate that the addition of vZVI nanoparticles produced strong reducing conditions, which accelerate removal of TPHs and suggest that these nanoparticles might be a promising technology to clean up TPHs contaminated water and soils.